# Simplify each of

(i)

= x2 - 3x2 – 3x + 5x + 5 - 7

= (2x2 – 3x2) - (6x + 5x) +

= x2 - +

= x2 - x +

(ii)

= 5 – 3x + 2y – 2x + y – 3x + 7y – 9

= - 8x + 10y – 4

(iii)

= x2y + x2y - xy2 - xy2 + xy + xy

= (165x2y + 2x2y) + (-126xy2 – 4xy2) +

= x2y - xy2 + xy

= x2y - xy2 + xy

(iv)

= y2 – 2y2 - y2 - y - y - y + 11 + 3 – 2

= (y2 – 6y2 + 2y2) - (4y – y – 2y) + 14 – 2

= y2 - y + 12

= -y2 – y + 12

= a2b2c - a2b2c + ab2c + ab2c - abc2 - abc2 + a2bc

= a2b2c + ab2c - abc2 + a2bc

Rate this question :

How useful is this solution?
We strive to provide quality solutions. Please rate us to serve you better.
Try our Mini CourseMaster Important Topics in 7 DaysLearn from IITians, NITians, Doctors & Academic Experts
Dedicated counsellor for each student
24X7 Doubt Resolution
Daily Report Card
Detailed Performance Evaluation
view all courses
RELATED QUESTIONS :

Subtract:

NCERT - Mathematics Exemplar

Take away:
</p
RD Sharma - Mathematics

Subtract 3x-4y-7zRD Sharma - Mathematics

Subtract:

RD Sharma - Mathematics

If we subtract -3NCERT - Mathematics Exemplar

<spanNCERT - Mathematics Exemplar

State whether theNCERT - Mathematics Exemplar